2012
DOI: 10.1155/2012/732816
|View full text |Cite
|
Sign up to set email alerts
|

Positive Modulation Effect of 8-Week Consumption ofKaempferia parvifloraon Health-Related Physical Fitness and Oxidative Status in Healthy Elderly Volunteers

Abstract: Health-related physical fitness declines as the age advances. Oxidative stress is reported to contribute the crucial role on this phenomenon. This condition is also enhanced by antioxidant. Therefore, we aimed to determine the effect of Kaempferia parviflora, a plant reputed for antifatigue, longevity promotion, and antioxidant effects, on health-related quality physical fitness and oxidative status of the healthy elderly volunteers. Total 45 subjects had been randomized to receive placebo or K. parviflora ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…MDA was estimated by determining the accumulation of Thiobarbituric Acid Reactive Substances (TBARS) (Wattanathorn et al, 2012) in the nerve homogenate whereas the activities of Superoxide Dismutase (SOD), Catalase (CAT) and Glutathione Peroxidase (GSH-Px) were determined by recording the ability to inhibit cytochrome C, the rate of decrease in H 2 O 2 and the amount of reduced Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidized per minute respectively (Jittiwat et al, 2009). …”
Section: Evaluation Of Oxidative Stress Markersmentioning
confidence: 99%
“…MDA was estimated by determining the accumulation of Thiobarbituric Acid Reactive Substances (TBARS) (Wattanathorn et al, 2012) in the nerve homogenate whereas the activities of Superoxide Dismutase (SOD), Catalase (CAT) and Glutathione Peroxidase (GSH-Px) were determined by recording the ability to inhibit cytochrome C, the rate of decrease in H 2 O 2 and the amount of reduced Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidized per minute respectively (Jittiwat et al, 2009). …”
Section: Evaluation Of Oxidative Stress Markersmentioning
confidence: 99%
“…A clinical report demonstrated that KPE effectively increased physical fitness in elderly subjects aged 60 or more [37]. Therefore, KPE may have more prominent effects on physical fitness and fatigue in elderly people and individuals lacking an exercise habit, among whom muscular metabolism has declined.…”
Section: Discussionmentioning
confidence: 99%
“…anti-inflammatory, antioxidant [18][19][20][21], anticancer [22,23], muscular metabolismenhancing [24], anti-photoaging [25], phosphodiesterase (PDE)5 inhibitory [26], anti-cardiovascular disease [27], and viral protease inhibitory [28] activities). A large number of studies have investigated the bioactivities of black ginger extract (KPE), which is rich in PMFs [24,[29][30][31][32][33][34][35][36][37]. We also reported that PMFs in KPE improved muscular metabolism through AMP-activated protein kinase (AMPK) activation in myocytes [24].…”
Section: Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations